Detection of Viral and Bacterial Respiratory Pathogens Identified by Molecular Methods in COVID-19 Hospitalized Patients and Its Impact on Mortality and Unfavorable Outcomes - Soto, Alonso (2021)
The research was funded by FONDECYT through the project Coinfeccion por patogenos respiratorios virales y bacterianos detectados por metodos moleculares en pacientes hospitalizados por COVID-19 y su impacto en la mortalidad y desenlaces desfavorables (Convenio N degrees 044-2020-FONDECYT) and Research Vice-chancellor of Universidad Ricardo Palma.